Non-symmetrized Hyperspherical Harmonics Method for Non-equal Mass Three-Body Systems - Nannini, Alessia; Marcucci, Laura E. (Frontiers in Physics, 2018)
The non-symmetrized hyperspherical harmonics method for a three-body system, composed by two particles having equal masses, but different from the mass of the third particle, is reviewed and applied to the ^3H, ^3He nuclei and ^3_ΛH hyper-nucleus, seen respectively as nnp, ppn and NNΛ three-body systems. The convergence of the method is first tested in order to estimate its accuracy. Then, the difference of binding energy between ^3H and ^3He due to the difference of the proton and the neutron masses is studied using several central spin-independent and spin-dependent potentials. Finally, the ^3_ΛH hypernucleus binding energy is calculated using different NN and Λ N potential models. The results have been compared with those present in the literature, finding a very nice agreement.